(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Vitamins and minerals are vital micronutrients that do not provide energy to the human body directly, yet they ensure energy metabolism, anabolic (plastic) processes, antioxidant protection, hormonal regulation, and immune-metabolic stability. This article systematically presents the fat-soluble and water-soluble groups of vitamins, the biochemical functions of macro- and microelements, their synergistic and antagonistic interactions, and the influence of the food matrix and technological processing on micronutrient bioavailability. In addition, metabolic risks associated with micronutrient deficiency and excess, as well as practical aspects of laboratory assessment based on biomarkers, are discussed. From a research perspective, viewing micronutrients as an integrative “enzyme-signal-tissue” network contributes to evidence-based dietary optimization and the development of functional food strategies.